Model of an automated control system for the positioning of radio signal transmission/reception devices - Bohdan Boriak; Alina Yanko; Oleksandr Laktionov (Радіоелектронні і комп'ютерні системи)
The concept of automated control systems for positioning radio-signal transmission and reception devices is discussed in this article. The subjects of this article are methods and means for ensuring precise and stable antenna positioning using web-based controllers with integrated sensors and actuators. This research aimed to develop a model of an automated control system for the positioning of radio signal transmission/reception antennas, including directional antennas with a radiation pattern angle of 60-90 degrees, ensuring the minimization of azimuth positioning error. The objective of this research is to develop automated antenna positioning systems using embedded systems. This article provides an example of the system's operation, where the controller performs antenna positioning tasks with high accuracy for directional antennas, such as Yagi–Uda antennas, ensuring that the azimuth position control error does not exceed 15 degrees. Positioning accuracy is achieved by a calibration procedure and dynamic servomotor adjustment based on the magnetometer data. This system is designed to ensure communication for operating a mobile robotic platform (unmanned vehicles), particularly in the presence of electromagnetic interference. Reliable communication with an unmanned vehicle depends on the positioning of the communication elements. It is a necessary condition for the operation of a mobile robotic platform, which, according to the classification by size groups, belongs to Micro, Mini, and Midi categories of wheeled vehicles and is used in search, rescue, and military operations. The result of the research is the development of the system, as well as its implementation and testing under laboratory conditions, which confirms the operability of the proposed control system model. Conclusions. This article discusses the concept of an automated control system for antenna positioning based on the use of embedded web technologies and their integration with hardware components that ensure precise positioning of radio-signal transmission/reception devices.